2020
DOI: 10.1002/fsn3.1847
|View full text |Cite
|
Sign up to set email alerts
|

The roles of banana peel powders to alter technological functionality, sensory and nutritional quality of chicken sausage

Abstract: Foods like meat, which have an animal origin, are typically a great source of protein, vitamins, essential fatty acids, and minerals required by the human body for good health and wellbeing. Changes like population growth, urbanization, economic, and market expansion create a higher demand for meat products. The global per capita meat consumption (average) has risen from 20 kg in 1961 to 43 kg in 2014 (Ritchie and Roser, 2017). In tropical and subtropical areas, banana is among the most cultivated and consumed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
21
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 64 publications
6
21
0
2
Order By: Relevance
“…For example, the incorporation of green banana peel flour ( Musa acuminata AAA ) into the fiber-enriched frankfurter-type sausage resulted in a reduction of cooking loss up to 4.1% keeping the texture, color, and other sensory characteristics intact, and these sausages qualify as potential alternatives for wheat allergic consumers . Recently, banana peel powder (BPP) of the Musa balbisiana variety was incorporated in chicken sausages (with 2% BPP), which delayed the lipid oxidation (due to antioxidant activity) by more than 50% in addition to the augmentation in nutritional value and water holding capacity . However, the aforementioned authors observed that BPP caused a reduction in fat content, darkening, and a hard texture in chicken sausage.…”
Section: Bp In Meat and Meat Productssupporting
confidence: 68%
See 1 more Smart Citation
“…For example, the incorporation of green banana peel flour ( Musa acuminata AAA ) into the fiber-enriched frankfurter-type sausage resulted in a reduction of cooking loss up to 4.1% keeping the texture, color, and other sensory characteristics intact, and these sausages qualify as potential alternatives for wheat allergic consumers . Recently, banana peel powder (BPP) of the Musa balbisiana variety was incorporated in chicken sausages (with 2% BPP), which delayed the lipid oxidation (due to antioxidant activity) by more than 50% in addition to the augmentation in nutritional value and water holding capacity . However, the aforementioned authors observed that BPP caused a reduction in fat content, darkening, and a hard texture in chicken sausage.…”
Section: Bp In Meat and Meat Productssupporting
confidence: 68%
“…80 Recently, banana peel powder (BPP) of the Musa balbisiana variety was incorporated in chicken sausages (with 2% BPP), which delayed the lipid oxidation (due to antioxidant activity) by more than 50% in addition to the augmentation in nutritional value and water holding capacity. 86 However, the aforementioned authors observed that BPP caused a reduction in fat content, darkening, and a hard texture in chicken sausage. Likewise, in another study with cooked fish patties, banana peel powder (BPP, 2, 4, and 6%) of the Musa balbisiana variety caused an improvement in the cooking yield, water holding capacity, and dietary fiber content.…”
Section: Bp In Meat and Meat Productsmentioning
confidence: 99%
“…Abbreviations: SBF2: Added 2% Saba banana peel; SBF4: Added 4% Saba banana peel; SBF6: Added 6% Saba banana peel; BBF2: Added 2% Berangan banana peel; BBF4: Added 4% Berangan banana peel; BBF6: Added 6% Berangan banana peel. Data for SBF2, SBF4 and SBF6 adapted from [4].…”
Section: Rheologymentioning
confidence: 99%
“…Therefore, the DF supplementation in foods, especially meat products, has been widely studied to provide a solution to increase the DF intake without extensively changing current eating habits [4]. Moreover, considering the nutritional benefit of a BP, it could be an excellent vehicle to improve the nutritional value of food, especially meat products.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that protein, sodium, calcium, potassium, and moisture were more over same. In a study it was concluded that the incorporation of banana peel powder to chicken sausage changed its properties and remained as a potential candidate as a value-adding ingredient which can be used during meat preparation as it positively influences the nutritional value and specific technological properties of the food [13]. Colour retention, enhanced flavor and texture was foundin samples with banana peel extract of 80% ethanol treatment and reported that the banana peelcan be used as a potential source to extend shelf stability [14].…”
Section: Nutrient Analysismentioning
confidence: 99%